Thoracic Segmental Spinal Anesthesia for Laparoscopic Cholecystectomy: A Case Report - Bajracharya, Nitendra Raj; Joshi, Pankaj; Neupane, Biplov; Shrestha, Reshma; KC, Milan; Parajuli, Bashudev (Journal of Institute of Medicine Nepal, 2024)
Laparoscopic surgery is normally performed under general anesthesia. Thoracic segmental spinal anesthesia (TSSA) can be a suitable alternative to general anesthesia for patients with respiratory diseases, as it avoids the risk of general anesthesia. We successfully managed a 74-year-old lady with COPD undergoing elective laparoscopic cholecystectomy with TSSA at T8-T9 interspace using 1.7 ml of hyperbaric bupivacaine 0.5% with 0.3 ml (15mcg) of fentanyl. Some discomfort was managed with 1mg midazolam and 50 mcg fentanyl intravenously. There was no neurological deficit and major hemodynamic fluctuations intra and post-operatively and recovery was uneventful.